THE EFFECT OF DIFFERENT PACKAGING ON THE CATFISH PROTEIN CONCENTRATE SAGOO NOODLE FORTIFIED WITH MICROALGAE (Chlorella sp.) AND CATFISH OIL (Pangasius hypopthalmus) STORED AT ROOM TEMPERATURE - Muhammad Khairi Hanafi; Syahrul '; Dewita Buchari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was intended to determine the effect of different packaging on the catfish proteinconcentrate sagoo noodle fortified with microalgae (Chlorella sp.) and catfish oil (Pangasiushypopthalmus) during room temperature storage. The method used in this study wasexperimental andcomposedas non factorial completely random design. Those were threetreatment, namely: A1 HDPE (high density polyethylene) packaging, A2 alumunium foilpackaging, and A3 is alumunium foil and HDPE combination packaging. Those were grouped for3 storage time, namely: B1 (day 0), B2 (days 15), dan B3 (days 30). The parameters used to assessthe quality of sagoo noodle were organoleptic value (consistence, flavor, aroma, and texture),water content, fat, peroxide value, and the total colony bacteria. The product packed by usingthe alumunium foil (A2) was showing the best quality, with characteristic of consistencewaswhite, catchy, whole and tidy. The flavor was specific sagoo noodle, the aroma was also specificsagoo noodle, and the texture was elastic, compact, whole and flexible.Keyword : Package, Sagoo noodle, Microalgae (Chlorella sp), Fish oil